Historical stories in children’s literature in Iraq (narrative production in the eighties as an example) - Muhammad, Sarah Mazin Qahtan (Journal of Humanities & Social Sciences, 2021)
This study aimed to highlight the historical story directed at child in Iraq during 1980s, a decade that witnessed a remarkable prosperity and development of children's literature. The study also focused on the role of Children's Culture House, the official sponsor of child's culture in Iraq, in presenting and enriching this kind of story. Moreover, the study explained the circumstances of that historical phase and its implications on the child's story in general and the historical story in particular. The study also covered the methods and means of writers in dealing with facts and events of history and presenting them to the child in line with the requirements of children's literature. The study then supported the theory with an artistic analysis of a historical story published at that point.
Keywords: children's literature; children's culture; historical story; children's culture house